2012
DOI: 10.1590/s1516-35982012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter production and nitrogen use efficiency of giant missionary grass in response to pig slurry application

Abstract: -This study assessed the effect of successive applications of pig slurry on the dry matter (DM) production and the nitrogen use efficiency of giant missionary grass along two years. A total of 55, 110, 165, 220 and 275 m 3 of pig slurry/ha/year were applied in order to supply 100, 200, 300, 400 and 500 kg of total N/ha/year, respectively. These treatments were compared with the ammonium nitrate (200 kg of N/ha/year) source of N and with a control (no nitrogen application).Annually, nitrogen was applied in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 11 publications
5
12
0
6
Order By: Relevance
“…The NAE obtained in this study was in the range reported by Vielmo et al (2011) for Tifton 85 (24 to 9 kg DM kg -1 N after fertilization with 144 and 576 kg N ha -1 year -1 , applied with 80 and 320 m 3 of pig slurry, respectively). Similar results were reported by Durigon et al (2002), of 6.6 (autumn) and 20.8 kg DM kg -1 N (spring) for a natural pasture, as well as to those reported by Miranda et al (2012) for giant missionary grass (19.0 kg DM kg -1 N from pig slurry; 30.3 kg DM kg -1 N from ammonium nitrate). The convergence between our results and those reported by these studies reinforces their consistency.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The NAE obtained in this study was in the range reported by Vielmo et al (2011) for Tifton 85 (24 to 9 kg DM kg -1 N after fertilization with 144 and 576 kg N ha -1 year -1 , applied with 80 and 320 m 3 of pig slurry, respectively). Similar results were reported by Durigon et al (2002), of 6.6 (autumn) and 20.8 kg DM kg -1 N (spring) for a natural pasture, as well as to those reported by Miranda et al (2012) for giant missionary grass (19.0 kg DM kg -1 N from pig slurry; 30.3 kg DM kg -1 N from ammonium nitrate). The convergence between our results and those reported by these studies reinforces their consistency.…”
Section: Resultssupporting
confidence: 90%
“…The PS doses were different between the years as a consequence of the N content in the manure, which changed in each period of application (Table 1). Positive and linear response to PS has been reported for natural pastures (Scheffer-Basso et al, 2008), Tifton 85 (Vielmo et al, 2011) and giant missionary grass (A. jesuiticus x A. scoparius) (Miranda et al, 2012). These reports and our results indicate 150 m 3 PS ha -1 (499 kg N ha -1 ) did not differ from the DMY obtained with ammonium sulfate (60 kg N ha -1 ).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations